Pneumococcal serotypes in adults hospitalized with community-acquired pneumonia in Greece using urinary antigen detection tests: the EGNATIA study, November 2017 - April 2019 - Adamantia Liapikou; Athanasios Konstantinidis; Vasiliki Kossyvaki; John Skiadas; Damianos Menegas; Cristina Méndez; Rohini Beavon; Elizabeth Begier; Bradford D. Gessner; Haralampos Milionis; Vasilios Tsimihodimos; Gerasimos Baxevanos; et al. (Taylor & Francis Group, 2022)
Greece introduced a 13-valent pneumococcal conjugate vaccine (PCV13) into the infant national immunization program in 2010 (3 + 1 schedule until June 2019). Since 2015, PCV13 has been recommended for adults aged 19-64 years with comorbidities and adults ≥65 years sequentially with 23-valent pneumococcal polysaccharide vaccine (PPSV23). We examined pneumococcal serotype distribution among Greek adults aged ≥19 years hospitalized with community-acquired pneumonia (CAP) during November 2017-April 2019. This was an interim analysis of EGNATIA, a prospective study of adult hospitalized CAP in the cities of Ioannina and Kavala. Pneumococcus was identified using cultures, BinaxNow®, serotype-specific urinary antigen detection assays (UAD-1/2). Our analysis included overall 482 hospitalized CAP patients (mean age: 70.5 years; 56.4% male). 53.53% of patients belonged to the highest pneumonia severity index (PSI) classes (IV-V). Pneumococcus was detected in 65 (13.5%) patients, with more than half (57%) of cases detected only by UAD. Approximately two-thirds of pneumococcal CAP occurred in those aged ≥65 years (n = 40, 8.3% of CAP). More than half of pneumococcal CAP (n = 35, 53.8%) was caused by PCV13 serotypes. Most frequently detected PCV13 serotypes were 3, 19A, 23F, collectively accounting for 83% of PCV13 vaccine-type (VT) CAP and 6% of all-cause CAP. Overall, 82.9% of PCV13 VT CAP occurred among persons with an indication (age/risk-based) for PCV13 vaccination. Even with a mature PCV13 childhood immunization program, a persistent burden of PCV13 VT CAP exists in Greek adults. Strategies to increase PCV13 (and higher-valency PCVs, when licensed) coverage in adults should be implemented to reduce the disease burden.